Order Flow and the Formation of Dealer Bids: An Analysis of Information and Strategic Behavior in the Government of Canada Securities Auctions - Samita Sareen; Ali Hortacsu (Fondazione Eni Enrico Mattei (FEEM), 2004)
Using data on Government of Canada securities auctions, this paper shows that in countries where direct access to primary issuance is restricted to government securities dealers, Order-flow" information is a key source of private information for these security dealers. Order-flow information is revealed to a security dealer through his interactions with customers, who can place bids in the auctions only through the security dealer. Since each dealer interacts with a different set of customers, they, in effect, see different portions of the market demand and supply curves, leading to differing private inferences of where the equilibrium price might.
Keywords: D82; G14; L88; 330; Treasury auctions; Behavioural finance; Staatspapier; Wertpapierhandel; Asymmetrische Information; Auktion; Kanada